Family History and Allergies as Risk Factors for Difficulty Eating in Children Aged 6-60 Months - Yudhasmara, Audi; Adani, Asrini Kaninta; Dewi, Ida Narulita; Judarwanto, Widodo; Yudhasmara, Sandiaz (Al Makki Health Informatics Journal, 2024)
Eating difficulties in children aged 6-60 months are often associated with family history and allergies. This study aims to analyze the risk factors of family history and allergies concerning eating difficulties in children in Malang City. This research used an observational analytic method with a cross-sectional design. One hundred thirty-eight children aged 6-60 months who participated in Posyandu activities were selected as the research sample. Data were collected through a questionnaire covering risk factors for eating difficulties, and the Pre-School Development Questionnaire (KPSP) was used to assess the children's development. Data analysis was performed using the chi-square test. The results showed a significant relationship between family history and allergies with eating difficulties in children (p<0.05). Children with a family history of eating difficulties or allergies were more likely to experience eating difficulties. In conclusion, family history and allergies are significant risk factors for eating difficulties in children aged 6-60 months, and early intervention can help prevent this problem. Further research is needed to explore other risk factors and more effective intervention strategies.